Fungal growth response to recurring heating events is modulated by species interactions - Lammel, Daniel R.; Szymczak, Aleksandra; Bielcik, Milos; Rillig, Matthias C. (Frontiers in Ecology and Evolution, 2023)
An increasing frequency of heat events can affect key organisms related to ecosystem functions. Soil saprobic fungi have important roles in carbon and nutrient cycling in soils, and they are clearly affected by heat events. When tested individually, saprobic soil fungi showed a variety of growth responses to a series of two heat events. However, in nature these fungi rarely grow alone. Coexistence theory predicts that diversity in the response to stressors can influence the outcome of species interactions and growth. This means that the co-cultivation of different fungi may affect their growth response to heat events. To test if recurring heat events affect fungal growth in small synthetic communities, we evaluated fungi previously known to respond to recurring heat events in experimental small communities composed of two and three species. For the fungi growing in pairs, surprisingly, most of the responses could not be predicted by how the isolates responded individually. In some cases, facilitation or increased competition were observed. For the three fungi growing together, results were also not predicted by the individual or pair responses. Both the heat events and the small communities influenced the growth of the fungi and growth properties emerged from the interactions among isolates and the heat stress. We show that not only do environmental conditions influence fungal interactions and growth rates, but also that the co-cultivation of different fungi affects fungal response to recurring heat events. These results indicate that more complex experimental designs are needed to better understand the effects of recurring heat events and climate change on soil fungi.